CARABID BEETLES FAUNA (COLEOPTERA, CARABIDAE) OF THE TSHETSHEN ISLAND IN THE CASPIAN SEA - I. A. Belousov; I. I. Kabak; G. M. Nakhibasheva; G. M. Mukhtarova; M. Rabadanov (Юг России: экология, развитие, 2014)
Aim. Carabid species (Coleoptera, Carabidae) are listed for Tshetshen Island in the Caspian Sea, Dagestan. The study is based on examination of 32799 adult carabids belonging to 123 species from 49 genera collected in 2011-1013. One species - Sirdenus grayii (Wollaston, 1862) – is firstly recorded from the territory ofDagestan.Location. Materials for the work served copies for the imago carabids,collected on the Chechen island in 2011-2012 years as staff and the students of ecologo-geografical faculty of Dagistan State University and the Institute for Applied Ecology (Makhachkala) Methods. Charges were made with the help of light traps, soil traps, including trap, enhanced light source .Geografpical coordinates of all locations were recorded using GPS- navigator: T1 - 43°57’58” N 47°38’35” E; T2 - 43°58’17” N 47°42’55”; T3 - 43°59’08” N 47°44’39” E; T4 - 43°57’27” N 47°45’05” E; Лагерь - 43°58’11”N47°38’46” E. Results. As a result of investigations indentified the species composition of the carabids of the island Chechen.Main conclusions. Total hectares of the Chechen island collected 32799 copies of the carabids, belonging to 123 species. Sirdenus grayii (Wollaston, 1862) –for the first time actuated in Dagestan.